The Time Series Properties of the Real Exchange Rates Between the Member States of the European Monetary Union - Rainer Maurer (Credit and Capital Markets – Kredit und Kapital, 2019)
The article "The Time Series Properties of the Real Exchange Rates Between the Member States of the European Monetary Union" analyses the time series behavior of the components of the real exchange rates between the founding member states of the EMU before and after the start of the EMU. Various panel and univariate country-specific tests show that the levels of these components are typically random walks. The resulting real exchange rates are also random walks and their components are not cointegrated. It is argued that these results question the operability of the EMU under the current policy regime in the long-run. One possibility to deal with this problem could be the suspension of the principle of a "single monetary policy". – – Die Zeitreiheneigenschaften der realen Wechselkurse der Mitgliedsländer der Europäischen Währungsunion Der Artikel "Die Zeitreiheneigenschaften der realen Wechselkurse der Mitgliedsländer der Europäischen Währungsunion" untersucht das Zeitreihenverhalten der Komponenten der realen Wechselkurse zwischen den Gründerstaaten der EWU vor und nach dem Beginn der EWU. Verschiedene Panel- und univariate länderspezifische Test zeigen, dass die Niveaus dieser Komponenten typischerweise Zufallspfaden folgen. Die resultierenden realen Wechselkurse folgen ebenfalls Zufallspfaden und ihre Komponenten sind nicht kointegriert. Diese Ergebnisse, so schließt der Artikel, stellen die langfristige Funktionsfähigkeit der EWU unter dem gegenwärtigen geldpolitischen Regime in Frage. Eine Möglichkeit, dieses Problem zu adressieren, könnte in der Preisgabe des Prinzips der einheitlichen Geldpolitik bestehen.
Keywords: E50; E31; C12; 330; Unit Root Tests; Cointegration Tests; Dutch disease; Real Exchange Rate; Deindustrialization; Purchasing Power Parity; Monetary Policy; European Monetary Union; European Central Bank; Single Monetary Policy